PREPARATION AND CHARACTERIZATION OF HYDROXYAPATITE BASED NANO-COMPOSITE BIOMORPHIC IMPLANTS - BARABÁS, Réka; RIGÓ, Melinda; ENISZNÉ-BÓDOGH, Margit; MOISA, Corina Florentina; CADAR, Oana (Studia Universitatis Babeș-Bolyai Chemia, 2018)
The aim of this study was the preparation and characterization of different biomorphic implants based on calcined cattle bones coated with hydroxyapatite (Hap) based nanocomposites in different ratios. For comparison, molded nanocomposites were also produced as biomorphic implants. The obtained nanocomposite/implants were characterized using X-ray diffraction, light microscopy and scanning electron microscopy, Brunauer-Emmett-Teller surface area and apparent porosity. The release of Ca and P in simulated body fluid was monitored by X-ray fluorescence. The adsorption capacity and extended-release dosage of implants were investigated with ibuprofen, an anti-inflammatory drug, by UV-VIS spectroscopy. The highest adsorption efficiency and stability were obtained for sintered (S) (Hap-) and 20% gelatin (G) nanocomposite (Hap-20G-S) and bone parts coated with Hap-S and Hap-20G-S nanocomposite, respectively. The best results (high adsorption efficiency and slow release - low desorption capacity) were obtained for molded Hap-20G-S composite, without bone. In summary, the cattle bones with hydroxyapatite coatings show great promise in production of inexpensive and patient-specific bone implants.